PERBANDINGAN PENGETAHUAN DAN SIKAP IBU HAMIL SETELAH DIBERIKAN KONSELING TENTANG TANDA BAHAYA KEHAMILAN - Tri Sundari, Dona; Vera Yuanita; Marini, Yoan (Jurnal Kesehatan dan Pembangunan, 2025)
Data from the World Health Organization (WHO) states that around 810 women die from complications related to pregnancy or childbirth worldwide every day, and around 295,000 women die during and after pregnancy and childbirth. Many efforts have been made to reduce the incidence, one of which is providing pregnancy danger sign counseling to help mothers better understand the signs of pregnancy danger. The purpose of this study was to determine the comparison of knowledge and attitudes of pregnant women after being given counseling about pregnancy danger signs. The design of this study used the quasi-experimental method. With a one group pretest-posttest design. The population of this study were all pregnant women. Sampling in this study was carried out by total sampling, namely the number of samples in this study was 50 respondents..The results obtained fromWilxocon knowledge statistical test obtained a p value = 0.000 <0.05. The results obtained from the Wilxocon attitude statistical test obtained a p value = 0.000 <0.05. The conclusion is that there is a comparison of knowledge and attitudes of pregnant women after being given counseling about pregnancy danger signs. Suggestions for health workers, the results of this study can be input for related parties such as local health workers who can provide direction to pregnant women to increase their knowledge about pregnancy danger signs in order to avoid these danger signs. Keywords: Knowledge, counseling, Pregnancy Danger Signs